Assessing the Teacher Emotions Scale in Chile: Does it relate to teachers’ well-being? / Evaluación de la Escala de Emociones Docentes en Chile: ¿Está relacionada con el bienestar docente? - Francisca Romo-Escudero; Paulina Guzmán; Jennifer LoCasale-Crouch; Ignacio Wyman; VARELA TORRES, JORGE JAVIER; Helma Koomen (My University, 2024)
Teachers’ emotions connect significantly to well-being, classroom practices and student relationships, addressing a gap in research primarily focused on English-speaking contexts. This study aims to bridge this gap by validating a Spanish version of the Teacher Emotions Scale (TES) among Chilean educators and investigating its relationship with well-being. The study employed an online questionnaire encompassing demographic details, TES assessments and well-being evaluations. TES adopts a discrete emotion approach, distinguishing nuanced differences between Enjoyment, Anger and Anxiety. Well-being was gauged through both Psychological well-being and Burnout scales. Confirmatory Factor Analysis (CFA) involving 2,689 participants affirmed the internal validity of TES, favoring a three-factor model (Enjoyment, Anger, Anxiety). TES factors consistently exhibited statistical significance, with specific factors predicting distinct well-being aspects. This pioneering study introduces a robust quantitative measure for understanding teachers’ emotional experiences in Spanish-speaking educational contexts, contributing valuable insights into the interplay between emotions, well-being and effective teaching practices.
Keywords: teachers' emotions; teachers' well-being; teacher emotions scale